Role of Glycine-to-Nitrate Ratio in Physical and Magnetic Properties of Zn-Ferrite Powder - Sami, We'am; Sadeq, Zainab Sabeeh (Iraqi Journal of Science, 2022)
We report the influence of different glycine-to-nitrate ratios on the physical and magnetic properties for synthesized zinc-ferrite by microwave-assisted combustion route. Phase impurity and surface morphology investigated with XRD analysis and field emission- scanning electron microscopy, indicated that spinel structure were formed.Average particles size increased with the decrease of glycine to nitrate ratio. Magnetic measurement results indicated that high values of saturation magnetization were produced with low glycine/nitrate ratio. Optical properties of the investigated ferrites exhibited photo absorption from UV to visible region with energy gap values that decreased with the decrease of glycine-to-nitrate ratio. Mainly two broad metal-oxygen bands for zinc-ferrite were seen in FT-IR spectra.